PENGARUH KOMUNIKASI TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT LUAHAGUNDRE MANIAMOLO - Marta Susanti Wau (Universitas Nias Raya, 2024)
This research uses associative quantitative research methods which aim to determine the effect performance at the luahagundre maniamolo subdistrict office. This research was conducted at the luahagundre maniamolo sub-district office with 31 employees as respondents. The analysis method used is simple linear regression analysis, where the value of the regression model Y = 59.924+0,119X. The results of this research show that communication has a significant effect on employee performance with values thitung = 1.031< ttabel = 1,699 with a significant level of o,311>0,05. Tis research can be concluded that communication influences employee performance at the luahagundre maniamolo sub-district office. Based on the results of the determination test that value Rsquare (R2) as big as 35% whereas 65% influenced by other vaeiables outside the model. The suggestions put forward by research are; 1) it is hoped that the leadership at the luahagundre maniamoo sub-district office will further improve good communication with employee in order to achieve maximum employee performance. 2) it is hoped that future researchers will focus more on others facthorsthat can influence employee performance at the luahagundre maniamolo sub-district.